Political change after the cold war : problems of the nation state and international relations in Europe and Asia - Everding, Ulrich; Everding, Ulrich (Colombo : Goethe-Institut, German Cultural Institute, 1992)
Papers presented at three different seminars between November 1990 and November 1991.
Cover title.
Keywords: Nation-state.; Europe -- Politics and government -- 1945-; Asia -- Politics and government -- 1945-